2017
DOI: 10.1111/vox.12521
|View full text |Cite
|
Sign up to set email alerts
|

Functionality testing of stem cell grafts to predict infectious complications after allogeneic hematopoietic stem cell transplantation

Abstract: Our results suggest that assaying T-cell function before HSCT could determine individual risks for infectious complications and thus aid in clinical decision-making regarding prophylactic and pre-emptive anti-infective therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Further, the median cytokine concentrations were higher in Aspergillus and CMV‐EBV‐Flu‐Tet peptide pool cultures than in tetanus‐toxoid cultures (Figure ). Nilsson et al . stimulated donor T cells with viral antigens and found that IL‐1β and IFN‐γ production was higher in grafts transplanted to recipients who had no post‐alloHSCT infectious complications compared to those who did.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the median cytokine concentrations were higher in Aspergillus and CMV‐EBV‐Flu‐Tet peptide pool cultures than in tetanus‐toxoid cultures (Figure ). Nilsson et al . stimulated donor T cells with viral antigens and found that IL‐1β and IFN‐γ production was higher in grafts transplanted to recipients who had no post‐alloHSCT infectious complications compared to those who did.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the median cytokine concentrations were higher in Aspergillus and CMV-EBV-Flu-Tet peptide pool cultures than in tetanus-toxoid cultures (Figure 4). Nilsson et al 38 stimulated donor T cells with viral antigens and found that IL-1b and IFN-c production was higher in grafts transplanted to recipients who had no post-alloHSCT infectious complications compared to those who did. While further assessment is required, the data presented indicate that cytokine profiles may have potential in infection risk stratification to individualise antimicrobial prophylaxis post-alloHSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Data set. To evaluate the TopS method, we selected for our analysis an available data set from experiments in immunology using multicolor flow cytometry 10,25 . We have used a publicly available high-dimensional data set where cell population identities are known from the expert manual gating.…”
Section: Methodsmentioning
confidence: 99%
“…The data was manually gated cell population labels as the reference populations. The Nilsson rare data contain rare population from bone marrow cells from healthy donor with 44,140 number of cells, 13 cell-surface markers and 358(0.8%) manually gated cells 10,25 . Data was transformed using arcsinh and TopS method as described in Sardiu et al 6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation